2013
DOI: 10.1002/hlca.201300079
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Reactions of Enamines Derived from Diphenylprolinol Silyl Ethers with Nitro Olefins and Lessons for the Corresponding Organocatalytic Conversions – a Survey

Abstract: The stoichiometric reactions of enamines prepared from aldehydes and diphenyl-prolinol silyl ethers (intermediates of numerous organocatalytic processes) with nitro olefins have been investigated. As reported in the last century for simple achiral and chiral enamines, the products are cyclobutanes (4 with monosubstituted nitro-ethenes), dihydro-oxazine N-oxide derivatives (5 with disubstituted nitroethenes), and nitro enamines derived from g-nitro aldehydes (6, often formed after longer reaction times). The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 130 publications
3
56
0
2
Order By: Relevance
“…Although the transition‐state model TS‐2 may also explain the diastereo‐ and enantioselectivities achieved, a more complicated sequence might exist during the reaction course. For example, we found that 14 exists as its cis isomer in CDCl 3 ( cis / trans =>99:1), whereas the trans isomer prevails in DMSO ( cis / trans =7:93) 11. The isomerization from cis to trans isomer might need to be considered.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the transition‐state model TS‐2 may also explain the diastereo‐ and enantioselectivities achieved, a more complicated sequence might exist during the reaction course. For example, we found that 14 exists as its cis isomer in CDCl 3 ( cis / trans =>99:1), whereas the trans isomer prevails in DMSO ( cis / trans =7:93) 11. The isomerization from cis to trans isomer might need to be considered.…”
Section: Resultsmentioning
confidence: 96%
“…The effect of acid additives : In our recent publication,11 we investigated the key Michael reaction of 2 with 3 or 14 , catalyzed by diphenylprolinol silyl ethers, in which the enamine generated from the α‐alkoxyaldehyde reacts with the nitroalkene to generate cyclobutane intermediates. The E / Z ratio of the enamine was found to be 1.0:1.6 and the E enamine preferentially reacts with ( E )‐ 3 , whereas the Z enamine reacts faster with ( Z )‐ 14 .…”
Section: Resultsmentioning
confidence: 99%
“…An acid may also activate the electrophile ( E + in Scheme ) in stage 2. It also has been reported that acid could catalyze the hydrolyses of ′′stable′′ intermediates (catalyst traps) to regenerate the chiral secondary amine catalyst 12. But the use of acid is not without problems.…”
Section: Methodsmentioning
confidence: 99%
“…On top of solvent phenomena, it is thus a real challenge to predict or explain the subtle configurational and conformational interplay between the electronic, orbital and steric states of a stereo‐defining event for a nucleophile‐catalyst‐electrophile triad within a complex milieu of organocatalytic equilibria, resting‐states, and additives 8. Nevertheless, a selection of enantioselective, 1,6‐conjugate additions3 are beginning to be discovered that proceed via remote, iminium‐mediated catalytic events (Scheme ) 9.…”
Section: Methodsmentioning
confidence: 99%